A layered software architecture for a flexible and smart organic rankine cycle (ORC) turbine : solutions and case study - Carsten Wolff and Mathias Knirr and Klaus-Peter Priebe and Peter Schulz and Jörn Strumberg (Information technology and control = Informacinės technologijos ir valdymas, 2018)
Intelligent Technical Systems are the consequent extension of the concept of Mechatronic Systems into the world of software-intensive, networked systems. The concept enhances the functionality and variability of physical (or electro-mechanical) technical systems by adding embedded electronics and software. This adds degrees of freedom (DoF) and controllability to the technical systems. It enhances the effectivity of integrating such systems into distributed infrastructures (e.g. smart grids) via a public network like the internet. Therefore, it enables them for an effective integration into the internet-of-things (IoT) since such Intelligent Technical Systems can add and draw significant functionality and optimisation potential from networking with other systems. They can become an integral part of a distributed system which is coupled via the IoT. Nevertheless, it is important to leverage between local control and distributed control carefully according to the requirements of the technical application. A smart heating grid is an example of a distributed cyber-physical system (CPS) which can be coupled via IoT. Such systems include components like block heat and power plants which produce electricity (fed into the public smart grid) and heat. Smart heating grids benefit from components which can convert heat into electricity in a flexible and controllable way and which can change fast from heat provision to electricity provision and vice-versa. An Organic Rankine Cycle (ORC) Turbine is such a component since it converts exhaust heat into electricity. This takes heat out of the heating grid and puts electricity into the electricity grid instead. Making such an ORC turbine intelligent means optimizing it for the usage in a smart heating grid. The challenge is to design a control software architecture which allows coupling via IoT on the required interaction level of the distributed system while guaranteeing a safe operation on the local level. The ar ticle is an extended version of a previous article at the ICIST conference. It presents the software architecture of an ORC turbine based on the architecture of the Operator-Controller-Module (OCM). Compared to the previous publication it provides a more in-depth presentation of the prototype implementation of the ORC turbine system. The OCM provides an architecture pattern which allows a seamless integration into a smart heating grid based on an IoT infrastructure while enabling maximum flexibility and efficiency of the local functionality of the turbine.
Keywords: Intelligent Technical Systems; Operator-Controller-Module (OCM); Organic Rankine Cycle (ORC) Turbine; Smart Heating Grid